Faktor Yang Mempengaruhi Kenakalan Pada Generasi Z Yang Berkuliah Di Semester 3 - Lestari, Ayu; Komalasari, Shanty (Universitas Negeri Surabaya, 2024)
Juvenile delinquency is an act that deviates from norms or regulations which is currently a common problem. This research aims to find out what factors influence juvenile delinquency in generation Z, especially students studying in semester 3. The type of research used is descriptive qualitative research where the researcher examines social phenomena by providing a detailed description. details regarding the matter being researched. The informants were two teenagers studying at University X. Data were collected using indirect interviews via telephone with the WhatsApp application. The data analysis technique uses three stages, namely data reduction, data presentation, and drawing conclusions. The results of this research are that the factors that influence juvenile delinquency in students are divided into two, namely internal factors and external factors. Internal factors include an identity crisis and weak self-control. Meanwhile, external factors include the family environment and friendship environment. These various factors influence juvenile delinquency and even when they become students they continue to do so. This research acts as a means of information that provides discussion of the factors that influence juvenile delinquency in students.